Stereoselective Construction of Glycosides Enabled by Glycosyl/ Glycal Metal Species - Wu, Xiaomei; Yan, Xin; Qian, Deyun (Synthesis, 2025)
Glycosyl/glycal metal functionalization has emerged as an efficient protocol for the construction of glycosides. Benefitting from the rapid development of organometallic chemistry and transition-metal-catalyzed cross-coupling reactions, glycosyl-metal-mediated glycosylation has significantly expanded the space for glycoside synthesis recently. In this short review, we underscore the representative progress in this area, categorizing the advancements by the type of glycosyl/glycal metal species. The reaction mechanism, stereochemical control, synthetic utility, and unmet challenges are also discussed.1 Introduction2 Glycosyl/Glycal Lithium-Based Glycosylations2.1 Preparation of Glycosyl/Glycal Lithium Reagents2.2 Glycosylation with Glycosyl/Glycal Lithiums3 Glycosyl/Glycal Stannane-Based Glycosylations3.1 Preparation of Glycosyl/Glycal Stannane Reagents3.2 Glycosylation with Glycosyl/Glycal Stannanes4 Glycosyl/Glycal Boron-Based Glycosylations4.1 Preparation of Glycosyl/Glycal Boron Compounds4.2 Glycosylation with Glycosyl/Glycal Boron Compounds5 Glycosylations Enabled by in situ Formed Glycosyl-Metal Intermediates5.1 Hydrofunctionalization of Glycals5.2 Functionalization/Glycosylation of Glycals6 Conclusion and Outlook
Keywords: glycosides; stereoselective glycosylation; glycosyl-metal species; cross-coupling; functionalization; carbohydrate chemistry